Method for repairing etching damage and method for improving opening performance of semiconductor device

By using high-temperature annealing and wet corrosion methods in vertical GaN power devices, etching damage is repaired and the trench sidewall morphology is optimized, which solves the leakage current and performance degradation caused by etching damage, and improves the device opening performance.

CN119446913APending Publication Date: 2025-02-14SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411583121.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In vertical GaN power devices, etching damage leads to deterioration of leakage current and trench characteristics, affecting the device's turn-on and shutdown performance.

Method used

High-temperature annealing is used to repair the damaged lattice and evenly distribute the surface defects, and then wet corrosion treatment is carried out to optimize the sidewall corrosion morphology of the trench structure.

Benefits of technology

Through the dual treatment of high-temperature annealing and wet corrosion, the morphological uniformity of the trench side wall is improved, the leakage problem is reduced, and the opening performance of semiconductor power devices is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446913A_ABST
    Figure CN119446913A_ABST
Patent Text Reader

Abstract

The invention discloses a method for repairing etching damage and a method for improving opening performance of a semiconductor device. The method for repairing the etching damage of the semiconductor material comprises the following steps: performing high-temperature annealing treatment on an etching region of the semiconductor material to decompose the surface of the semiconductor material in the etching region so as to repair crystal lattices of the etching damage and uniformly distribute surface defects of the etching region; and carrying out wet etching treatment on the etching region of the semiconductor material. According to the method, high-temperature annealing pretreatment is utilized before wet etching, the side wall corrosion morphology of the groove-shaped structure formed through etching is optimized, side wall prisms are distributed more evenly, and meanwhile the problem of electric leakage of the semiconductor power device is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention particularly relates to a method for repairing etching damage and a method for improving the turn-on performance of a semiconductor device, belonging to the technical field of wide bandgap semiconductor materials and devices. Background Art

[0002] In recent years, vertical semiconductor (Gallium Nitride, GaN) power devices have made great progress in breakdown voltage, current density and dynamic performance. In vertical GaN power devices, the trench structure is conducive to achieving lower leakage current and more novel device structure design. Specifically, for vertical trench gate metal oxide semiconductor transistors (Metal-Oxide-Semiconductor Field Effect Transitor, MOSFET), the surface characteristics of the trench sidewall play a crucial role in the opening and closing of the device. However, it is worth noting that in general processes, the formation of the trench is often achieved by inductively coupled plasma etching (Inductively Coupled Plasma, ICP). The damage caused during the etching process will lead to the degradation of leakage current and trench characteristics. In addition, the trench sidewall serves as a channel for carrier migration, and the sidewall morphology also significantly affects the electric field distribution, thereby affecting the on-state and off-state performance. In the MOS structure, the defects generated by etching in the gate dielectric and at the interface between the gate dielectric and the semiconductor exist in the form of positive charges, which will not only cause a negative drift in the device threshold voltage and reduce the reliability of the device, but also increase the probability of Coulomb scattering, thereby reducing the channel mobility close to the etched surface. At the same time, the morphology of the trench sidewall also has roughness scattering, which affects the turn-on performance of the device.

[0003] A more common repair method is to use tetramethylammonium hydroxide (TMAH) solution to wet-etch the sidewalls, process and repair etching damage. Due to the anisotropic corrosion characteristics of GaN in an alkaline environment, its corrosion morphology is inconsistent in different non-polar surfaces. In vertical devices, the non-polar a-plane and non-polar c-plane are often used as channel sidewalls. After wet etching, the characteristics of the sidewalls are presented as prisms distributed longitudinally and transversely, respectively, and the prism density is also different. This prism feature orientation and prism density greatly affect the carrier migration rate. Although the use of TMAH solution can improve the damage of the etching surface to a certain extent, the corrosion features left on different non-polar surfaces have caused deterioration in the opening of the device. In the non-polar a-plane, this corrosion feature distribution is distributed along the longitudinal direction. GaN itself has many epitaxial defects, and this defect will cause the corrosion rate at different positions to be inconsistent during the corrosion process, resulting in uneven distribution of corrosion features. This phenomenon is not conducive to the opening performance of the device. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for repairing etching damage and a method for improving the turn-on performance of a semiconductor device, thereby overcoming the deficiencies in the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The first aspect of an embodiment of the present invention provides a method for repairing etching damage to a semiconductor material, comprising: first performing a high-temperature annealing treatment on the etched area of ​​the semiconductor material to decompose the surface of the semiconductor material in the etched area to repair the lattice damaged by the etching, while making the surface defects of the etched area evenly distributed; and then performing a wet etching treatment on the etched area of ​​the semiconductor material.

[0006] A second aspect of an embodiment of the present invention provides a method for improving the turn-on performance of a vertical semiconductor power device, wherein a gate region of an epitaxial structure layer of the vertical semiconductor power device has a groove structure formed by etching, and the method comprises: after etching the gate region of the epitaxial structure layer to form the groove structure, using the method for repairing etching damage to the semiconductor material to repair the groove structure.

[0007] Compared with the prior art, the advantages of the present invention include: The present invention utilizes high temperature annealing pretreatment before wet etching to optimize the sidewall corrosion morphology of the groove structure formed by etching, so that the sidewall prisms are distributed more evenly. At the same time, the present invention also optimizes the leakage problem of semiconductor power devices.

[0008] The present invention first performs high-temperature annealing treatment on the groove-shaped structure formed by etching of the semiconductor material, and then performs wet etching treatment. The high-temperature degradation process can repair the lattice damaged by etching and redistribute the defects, which is more conducive to the uniformity of wet etching, thereby making the distribution of corrosion characteristics more uniform. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is a schematic structural diagram of a semiconductor sample with a groove structure provided in a typical implementation case of the present invention; Figure 2a , Figure 2b , Figure 2c , Figure 2d These are the SEM images of the sidewall morphology of the groove-like structure obtained after different treatments; Figure 3 It is a schematic diagram of the structure of a vertical diode; Figure 4 These are the leakage curves of multiple vertical diodes. DETAILED DESCRIPTION

[0010] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0011] The first aspect of an embodiment of the present invention provides a method for repairing etching damage to a semiconductor material, comprising: first performing a high-temperature annealing treatment on the etched area of ​​the semiconductor material to decompose the surface of the semiconductor material in the etched area to repair the lattice damaged by the etching, while making the surface defects of the etched area evenly distributed; and then performing a wet etching treatment on the etched area of ​​the semiconductor material.

[0012] Furthermore, the semiconductor material includes III-V group nitride materials. Specifically, the method provided by the present invention can be applicable to hexagonal semiconductor materials. For example, the semiconductor material can be gallium nitride.

[0013] Furthermore, during the high-temperature annealing process, the defects of the semiconductor material are decomposed and re-adsorbed on the surface of the semiconductor material. In this process, the lattice destroyed by the bombardment of etching ions is repaired, and the defects are redistributed and tend to be evenly distributed.

[0014] Furthermore, the high temperature annealing treatment must ensure that the semiconductor material has a certain surface decomposition, so the annealing temperature should be close to the growth temperature of the semiconductor material. When the semiconductor material is gallium nitride, the temperature of the high temperature annealing treatment is 800°C~875°C, and the time is 10min~30min.

[0015] Furthermore, the high temperature annealing treatment is carried out in multiple times, the temperature of the multiple high temperature annealing treatments is the same, and the time of each high temperature annealing treatment is not less than 2 minutes to ensure the integrity of the surface decomposition process of the semiconductor material. Preferably, the time of each high temperature annealing treatment is 2 minutes to 5 minutes.

[0016] Furthermore, the duration of the multiple high temperature annealing treatments is the same.

[0017] Furthermore, the time interval between multiple high temperature annealing treatments is 1-2 minutes.

[0018] Furthermore, the protective gas atmosphere includes a nitrogen atmosphere, and the nitrogen flow rate must ensure that the annealing environment is mainly a nitrogen-rich environment, so the nitrogen flow rate should not be less than 20 sccm.

[0019] Furthermore, the wet etching process includes: immersing the semiconductor material after the high temperature annealing process in an etching solution and heating it in a water bath.

[0020] Furthermore, the etching solution includes tetramethylammonium hydroxide solution or phosphoric acid solution.

[0021] Furthermore, the etching region of the semiconductor material is formed by dry etching.

[0022] Furthermore, the dry etching includes inductively coupled plasma etching, reactive ion etching, magnetic neutral line plasma etching and other plasma etching methods.

[0023] A second aspect of an embodiment of the present invention provides a method for improving the turn-on performance of a vertical semiconductor power device, wherein a gate region of an epitaxial structure layer of the vertical semiconductor power device has a groove structure formed by etching, and the method comprises: after etching the gate region of the epitaxial structure layer to form the groove structure, using the method for repairing etching damage to the semiconductor material to repair the groove structure.

[0024] Furthermore, the groove structure is formed by dry etching.

[0025] Furthermore, the groove structure is formed by a plasma etching method such as inductively coupled plasma etching, reactive ion etching, magnetic neutral line plasma etching, etc.

[0026] Furthermore, the vertical semiconductor power device includes a vertical trench gate metal oxide semiconductor transistor.

[0027] The technical solution, its implementation process and principle, etc. will be further explained below in conjunction with the accompanying drawings and specific implementation cases. In the following comparative examples and embodiments, gallium nitride materials / samples are taken as examples. Unless otherwise specified, the etching process and its equipment, high-temperature annealing equipment, and the structure of the vertical gallium nitride power device used in the embodiments of the present invention are all known in the art and are not specifically limited or explained here.

[0028] Comparative Example 1 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0029] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0030] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0031] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0032] Through the above three steps, a groove-shaped structure can be formed.

[0033] 3) Wet etching of the etched GaN samples: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0034] Example 1 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) Forming a gallium nitride structure layer 2 on a substrate 3 to form a gallium nitride sample, such as Figure 1 As shown, the substrate 3 may be a homogeneous substrate (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0035] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0036] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0037] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0038] Through the above three steps, a groove-shaped structure can be formed.

[0039] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0040] The etched GaN sample was subjected to high temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing was a nitrogen atmosphere, the nitrogen flow rate was 20 sccm, the annealing temperature was 850°C, and the annealing time was 20 min.

[0041] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0042] GaN is a hexagonal crystal structure. Depending on the different orientations of the crystal plane and the central axis (c-axis, vertical direction), it can have polar and non-polar planes. The plane perpendicular to the c-axis is called a polar plane, such as the c-plane, and the plane parallel to the c-axis is called a non-polar plane, such as the a-plane and the c-plane. The sidewalls of the groove-shaped structure formed on the GaN material are mostly taken on the non-polar plane.

[0043] In the scheme of comparative example 1, after the sidewall of the groove structure is wet-etched, due to the anisotropy of GaN during the etching process, the morphological characteristics of the sidewall of the groove structure will be different due to the different non-polar planes. Taking the non-polar a-plane as an example, the sidewall morphology of the groove structure of the gallium nitride sample obtained in comparative example 1 is as follows: Figure 2aAs shown in FIG. 1 , it can be seen that after the sidewall surface is etched, vertical prisms distributed along the c-axis direction are present, and these prisms are of different heights and sizes. Example 1 is subjected to high temperature annealing treatment before wet etching. The sidewall morphology of the groove structure of the gallium nitride sample obtained in Example 1 is as follows: Figure 2b As shown by Figure 2b It can be seen that the sidewall morphology features have become more uniform, and the height and size of the vertical prisms remain consistent. This is mainly because the high-temperature annealing process repairs the lattice and redistributes the defects, making the wet etching process more uniform, thereby effectively improving the sidewall morphology of the groove structure.

[0044] Example 2 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0045] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0046] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0047] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0048] Through the above three steps, a groove-shaped structure can be formed.

[0049] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0050] The etched GaN sample was subjected to high temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing was a nitrogen atmosphere, the nitrogen flow rate was 20 sccm, the annealing temperature was 800°C, and the annealing time was 20 min.

[0051] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0052] Example 3 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0053] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0054] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0055] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0056] Through the above three steps, a groove-shaped structure can be formed.

[0057] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0058] The etched GaN sample was subjected to high temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing was a nitrogen atmosphere, the nitrogen flow rate was 20 sccm, the annealing temperature was 900°C, and the annealing time was 20 min.

[0059] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0060] Example 4 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0061] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0062] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0063] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0064] Through the above three steps, a groove-shaped structure can be formed.

[0065] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0066] The etched gallium nitride sample was subjected to high-temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high-temperature annealing was a nitrogen atmosphere with a nitrogen flow rate of 20 sccm. The high-temperature annealing was repeated four times. Each annealing temperature was 850°C and the annealing time was 5 minutes. The time interval between the four high-temperature annealings was 1 minute.

[0067] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0068] Example 5 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0069] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0070] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0071] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0072] Through the above three steps, a groove-shaped structure can be formed.

[0073] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0074] The etched gallium nitride sample was subjected to high-temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high-temperature annealing was a nitrogen atmosphere with a nitrogen flow rate of 20 sccm. The high-temperature annealing was repeated twice, each with an annealing temperature of 850°C and an annealing time of 10 minutes. The time interval between the two high-temperature annealings was 2 minutes.

[0075] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0076] Example 6 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0077] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0078] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0079] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0080] Through the above three steps, a groove-shaped structure can be formed.

[0081] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0082] The etched gallium nitride sample was subjected to high temperature annealing treatment in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing treatment was a nitrogen atmosphere with a nitrogen flow rate of 20 sccm. The high temperature annealing treatment was repeated once, each annealing temperature was 850°C, and the annealing time was 20 min.

[0083] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0084] Comparative Example 2 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) Forming a gallium nitride structure layer 2 on a substrate 3 to form a gallium nitride sample, such as Figure 1 As shown, the substrate 3 may be a homogeneous substrate (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0085] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0086] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0087] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0088] Through the above three steps, a groove-shaped structure can be formed.

[0089] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0090] The etched GaN sample was subjected to high temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing was a nitrogen atmosphere. The nitrogen flow rate was 20 sccm, the annealing temperature was 950°C, and the annealing time was 20 min.

[0091] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0092] Comparative Example 3 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) Forming a gallium nitride structure layer 2 on a substrate 3 to form a gallium nitride sample, such as Figure 1As shown, the substrate 3 may be a homogeneous substrate (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0093] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0094] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0095] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0096] Through the above three steps, a groove-shaped structure can be formed.

[0097] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0098] The etched GaN sample was subjected to high temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing was a nitrogen atmosphere, the nitrogen flow rate was 20 sccm, the annealing temperature was 750°C, and the annealing time was 20 min.

[0099] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0100] Comparative Example 4 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) Forming a gallium nitride structure layer 2 on a substrate 3 to form a gallium nitride sample, such as Figure 1 As shown, the substrate 3 may be a homogeneous substrate (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0101] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0102] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0103] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0104] Through the above three steps, a groove-shaped structure can be formed.

[0105] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0106] The etched gallium nitride sample was subjected to high temperature annealing treatment in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing treatment was a nitrogen atmosphere, the nitrogen flow rate was 20 sccm, the annealing temperature was 850°C, and the annealing time was 5 min.

[0107] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0108] Comparative Example 5 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0109] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0110] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0111] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0112] Through the above three steps, a groove-shaped structure can be formed.

[0113] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0114] The etched gallium nitride sample was subjected to high-temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high-temperature annealing was a nitrogen atmosphere with a nitrogen flow rate of 20 sccm. The high-temperature annealing was repeated four times. Each annealing temperature was 900°C and the annealing time was 20 minutes. The time interval between the four high-temperature annealings was 2 minutes.

[0115] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0116] Comparative Example 6 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0117] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0118] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0119] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0120] Through the above three steps, a groove-shaped structure can be formed.

[0121] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0122] The etched gallium nitride sample was subjected to high-temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high-temperature annealing was a nitrogen atmosphere with a nitrogen flow rate of 20 sccm. The high-temperature annealing was repeated four times. Each annealing temperature was 850°C and the annealing time was 5 minutes. The time interval between the four high-temperature annealings was 2 minutes.

[0123] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0124] Comparative Example 7 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0125] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0126] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0127] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0128] Through the above three steps, a groove-shaped structure can be formed.

[0129] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0130] The etched gallium nitride sample was subjected to high temperature annealing treatment in a rapid annealing furnace. The annealing atmosphere of the high temperature annealing treatment was a nitrogen atmosphere with a nitrogen flow rate of 20 sccm. The high temperature annealing treatment was repeated once, each annealing temperature was 850°C, and the annealing time was 5 minutes.

[0131] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0132] Comparative Example 8 A method for processing a gallium nitride sample with a groove structure comprises the following steps: 1) A gallium nitride structure layer 2 is formed on a substrate 3 to form a gallium nitride sample. The substrate 3 may be a homogeneous (intrinsic GaN) or a heterogeneous substrate, such as sapphire, silicon or silicon carbide.

[0133] 2) Etching the GaN structure layer 2 to form a groove structure. The specific process of the etching process mainly includes the following three stages: Deposition of SiO2 hard mask: A layer of SiO2 is deposited on the surface of the GaN structure layer 2 using a thin film deposition device to form a SiO2 hard mask. The thickness of the SiO2 hard mask is determined according to the required etching depth of the GaN structure layer 2, and is generally the same as or greater than the etching depth.

[0134] SiO2 hard mask patterning: The SiO2 hard mask is etched using F-based gas to achieve mask patterning and expose the gallium nitride structure layer 2 under the mask.

[0135] Transfer of etching pattern: Use Cl-based gas to etch the GaN structure layer 2 to a specified depth, ensuring that there is a residual SiO2 mask on the surface to protect the unetched area.

[0136] Through the above three steps, a groove-shaped structure can be formed.

[0137] 3) Repair the etched GaN samples. The repair process includes two stages: High temperature annealing treatment: The etched GaN samples were cleaned with an organic cleaning agent to ensure that the surface contained no residual photoresist and only the unetched SiO2 mask remained.

[0138] The etched gallium nitride sample was subjected to high-temperature annealing in a rapid annealing furnace. The annealing atmosphere of the high-temperature annealing was a nitrogen atmosphere with a nitrogen flow rate of 20 sccm. The high-temperature annealing was repeated four times. Each annealing temperature was 850°C and the annealing time was 20 minutes. The time interval between the four high-temperature annealings was 10 minutes.

[0139] After the above annealing treatment, the sample is subjected to wet etching treatment: The GaN sample was immersed in a 25wt% TMAH solution and heated in a water bath. The temperature of the water bath was 85°C and the corrosion time was 2 hours.

[0140] Figure 2a , Figure 2b , Figure 2c , Figure 2d These are the SEM images of the sidewall morphology of the groove structure obtained after different treatments. Four representative images are selected here for emphasis. Figure 2a This is the side wall morphology of the groove-like structure obtained in Comparative Example 1 without annealing treatment. It can be seen that the prism heights on the side wall surface are uneven and the prism sizes are also different; Figure 2b This is the side wall morphology of the groove-like structure obtained after annealing in Example 1 of the present invention. It can be seen that the distribution of prisms on the side wall surface is significantly improved, the height and size are unified, and the side wall becomes flatter; Figure 2cThis is the sidewall morphology of the groove structure obtained when the annealing temperature is lower than 800°C in Comparative Example 3. Figure 2d This is the side wall morphology of the groove-like structure obtained in Example 4 due to insufficient annealing time. It can be seen that due to insufficient annealing temperature or processing time, the uneven distribution of prisms on the side wall surface still exists.

[0141] The gallium nitride samples with groove structures obtained in Examples 1-6 and Comparative Examples 1-8 were processed to form vertical diodes with the same structure and parameters as test devices. The gallium nitride samples were used as epitaxial structures of the vertical diodes. The structures of the vertical diodes were as follows: Figure 3 As shown in FIG. 1 , the leakage current of the plurality of vertical diodes is measured and obtained respectively. The lower the leakage current level, the better the device performance. The leakage current curves of the plurality of vertical diodes are shown in FIG. Figure 4 As shown. Wherein, EDL, REF: conventional diode off-state performance curve in reference [Nie H, Diduck Q, Alvarez B, et al. 1.5kV and 2.2mΩ·cm2 VerticalGaN transistors on bulk GaN substrates[J]. IEEE Electron Device Letters, 2014, 35(9):939-941]. Example 1 shows the lowest leakage level, and the relative leakage levels of other examples and comparative examples are increased, among which comparative examples 6 and 8 have the highest leakage levels (<100V), and comparative examples 1 and 3 are moderate, which is consistent with the SEM image observation results above.

[0142] The present invention utilizes high temperature annealing pretreatment before wet etching to optimize the sidewall corrosion morphology of the groove structure formed by etching, so that the sidewall prisms are distributed more evenly. At the same time, the present invention also optimizes the leakage problem of semiconductor power devices.

[0143] The present invention first performs high-temperature annealing treatment on the groove-shaped structure formed by etching of the semiconductor material, and then performs wet etching treatment. The high-temperature degradation process can repair the lattice damaged by etching and redistribute the defects, which is more conducive to the uniformity of wet etching, thereby making the distribution of corrosion characteristics more uniform.

[0144] The present invention improves the device mobility, enhances the device stability, and further improves the device turn-on performance. Specifically, the size of the mobility is particularly important in the device turn-on performance. On the one hand, it affects the saturation current size and switching frequency of the device. The mobility will be affected by the Coulomb scattering and roughness scattering caused by dry etching damage. Repairing the damage can greatly improve the mobility.

[0145] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for repairing damage to the etched surface of a semiconductor material, characterized in that: include: First, the etched area of ​​the semiconductor material is subjected to high temperature annealing treatment to decompose the surface of the semiconductor material in the etched area, so as to repair the lattice damaged by etching and make the surface defects of the etched area uniformly distributed; Then, the etched area of ​​the semiconductor material is subjected to wet etching treatment.

2. The method for repairing etching damage of semiconductor materials according to claim 1, characterized in that: The atmosphere of the high temperature annealing treatment is a protective gas atmosphere, the temperature of the high temperature annealing treatment is 800° C. to 875° C., and the time is 10 min to 30 min.

3. The method for repairing etching damage of semiconductor materials according to claim 1 or 2, characterized in that: The high temperature annealing treatment is performed in multiple times, the temperature of the multiple high temperature annealing treatments is the same, and the time of each high temperature annealing treatment is not less than 2 minutes. Preferably, the time of each high temperature annealing treatment is 2 minutes to 5 minutes.

4. The method for repairing etching damage of semiconductor materials according to claim 3, characterized in that: The time of the multiple high temperature annealing treatments is the same.

5. The method for repairing etching damage of semiconductor material according to claim 3, characterized in that: The time interval between multiple high temperature annealing treatments is 1-2 min.

6. The method for repairing etching damage of semiconductor materials according to claim 2, characterized in that: The protective gas atmosphere includes a nitrogen atmosphere; Preferably, the nitrogen gas flow rate is not less than 20 sccm.

7. The method for repairing etching damage of semiconductor materials according to claim 1, characterized in that: The wet etching process comprises: immersing the semiconductor material after high temperature annealing in an etching solution and heating it in a water bath; Preferably, the etching solution includes tetramethylammonium hydroxide solution or phosphoric acid solution.

8. The method for repairing etching damage of semiconductor materials according to claim 1, characterized in that: The etched region of the semiconductor material is formed by dry etching; Preferably, the dry etching includes inductively coupled plasma etching.

9. A method for improving the turn-on performance of a vertical semiconductor power device, wherein the gate region of the epitaxial structure layer of the vertical semiconductor power device has a trench structure formed by etching, characterized in that: The method comprises: after etching a gate region of an epitaxial structure layer to form a trench structure, using the method for repairing etching damage of a semiconductor material as described in any one of claims 1 to 8 to repair the trench structure.

10. The method for improving turn-on performance of a vertical semiconductor power device according to claim 9, characterized in that: The groove structure is formed by dry etching; Preferably, the groove structure is formed by inductively coupled plasma etching; Preferably, the vertical semiconductor power device comprises a vertical trench gate metal oxide semiconductor transistor.